Rola rodziny w kształtowaniu ról i stereotypów płciowych - Palus, Katarzyna (Wydawnictwo Naukowe UAM, 2006)
The purpose of the current paper is to present the role of family in the formation of sex-roles and stereotypes. Family environment plays a vital role in the socialization of children's gender roles. Parents not only transmit to their children the gender attitudes and stereotypes that are present in our society, but also create and activate these stereotypes. Many researchers highlitght children's dyadic family relationship experiences with their parents and siblings. Family is a part of a larger context ranging from social attitudes and values and economic opportunities both for men and women. Thus, it cannot be regarded as being isolated from this wider context. The parents' role in the socialization of children's gender roles is multidimensional and it is connected with a variety of social mechanisms such as modeling, observation and learning through the effects of rewarding and punishing consequences of demonstrated gender behaviors.
The role of family in the formation of sex-roles and stereotypes